2006
DOI: 10.1111/j.1365-2230.2006.02243.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil respiratory burst is decreased in scleroderma and normalized by near-infrared mediated hyperthermia

Abstract: Neutrophils and monocytes do not exhibit cell-autonomous overproduction of ROS in scleroderma, thereby implicating fibroblasts as main source for clinically relevant ROS accumulation. Furthermore, repeated mild infrared-mediated hyperthermia exerts a lasting cell-type-specific effect on neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…The data are contradictory and are largely limited by old-fashioned neutrophil isolation procedures which can lead to neutrophil activation 16 17. A recent study has, however, shown that neutrophils produce less reactive oxygen species in vitro than control neutrophils when unstimulated 18. In agreement with this, we have found that neutrophils from patients with SSc are hypofunctional in tests of reactive oxygen species generation and chemotaxis (unpublished data).…”
Section: Introductionsupporting
confidence: 75%
“…The data are contradictory and are largely limited by old-fashioned neutrophil isolation procedures which can lead to neutrophil activation 16 17. A recent study has, however, shown that neutrophils produce less reactive oxygen species in vitro than control neutrophils when unstimulated 18. In agreement with this, we have found that neutrophils from patients with SSc are hypofunctional in tests of reactive oxygen species generation and chemotaxis (unpublished data).…”
Section: Introductionsupporting
confidence: 75%
“…In similarity with all inflammatory diseases, there is an increase in oxidative stress in blood and target tissue also in Ps and scleroderma but this should not necessarily be interpreted as a causative factor. In fact, it has been reported that the respiratory burst was reduced in neutrophils of scleroderma patients and a recent report of imiquimod‐induced psoriatic dermatitis showed a protective role by ROS, which was accompanied by increased IDO expression and Foxp3 + regulatory T‐cell frequency . Our findings suggest that mounting normal levels of ROS are vital in regulating the inflammatory response to mannan, otherwise this will lead to aberrant inflammation that precipitates in skin and joints.…”
Section: Ros Regulation Of Inflammatory Diseases – Innate Immunitysupporting
confidence: 57%
“…The data are contradictory and largely limited by old-fashioned neutrophil isolation procedures that can lead to neutrophil activation [9, 10]. A recent study has, however, shown that neutrophils produce less reactive oxygen species in vitro compared with control neutrophils when unstimulated [11]. In agreement with this we have found that neutrophils from patients with SSc are hypofunctional in tests of reactive oxygen species generation and chemotaxis (unpublished data).…”
Section: Introductionsupporting
confidence: 76%